Long-Lived Species of Bivalves Exhibit Low MT-DNA Substitution Rates - Mortz, Mathieu; Levivier, Aurore; Lartillot, Nicolas; Dufresne, France; Blier, Pierre U. (Frontiers in Molecular Biosciences, 2021)
Bivalves represent valuable taxonomic group for aging studies given their wide variation in longevity (from 1-2 to >500 years). It is well known that aging is associated to the maintenance of ROS homeostasis and that mitochondria phenotype and genotype dysfunctions accumulation is a hallmark of these processes. Previous studies have shown that mitochondrial DNA mutation rates are linked to lifespan in vertebrate species, but no study has explored this in invertebrates. To this end, we performed a Bayesian Phylogenetic Covariance model of evolution analysis using 12 mitochondrial protein-coding genes of 76 bivalve species. Three life history traits (maximum longevity, generation time and mean temperature tolerance) were tested against (1) synonymous substitution rates (dS), (2) conservative amino acid replacement rates (Kc) and (3) ratios of radical over conservative amino acid replacement rates (Kr/Kc). Our results confirm the already known correlation between longevity and generation time and show, for the first time in an invertebrate class, a significant negative correlation between dS and longevity. This correlation was not as strong when generation time and mean temperature tolerance variations were also considered in our model (marginal correlation), suggesting a confounding effect of these traits on the relationship between longevity and mtDNA substitution rate. By confirming the negative correlation between dS and longevity previously documented in birds and mammals, our results provide support for a general pattern in substitution rates.